FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENUMPANG MASKAPAI: ANALISIS PENGARUH KECEPATAN PELAYANAN, KERAMAHAN PETUGAS, DAN KEJELASAN INFORMASI DI CHECK-IN COUNTER - Butar Butar, Inri Desniti Nuggetty; Arum, Adinda Sekar; Sundoro, Sundoro (Journal of Governance and Public Administration, 2025)
In the face of increasingly fierce competition in the airline industry, passenger satisfaction is a key element for an airline's success. This study aims to evaluate the influence of three main factors in check-in desk services, namely Service Speed, Officer Friendliness, and Information Clarity on Passenger Satisfaction. The approach in this article is qualitative using library research techniques. The research findings (hypothetical) reveal that the three independent variables of Service Speed, Officer Friendliness, and Information Clarity both individually and together have a positive and significant effect on Passenger Satisfaction. This conclusion makes it clear that efforts to improve service quality in these three aspects are a fundamental and effective strategic step for the airline in increasing overall passenger satisfaction and loyalty.